Cryptosporidiosis in a transplant recipient with severe intractable diarrhea: Detection of Cryptosporidium oocysts by intestinal biopsies. Issue 2 (25th January 2018) - Kagawa, Kumiko; Fujino, Hikaru; Miki, Hirokazu; Sogabe, Kimiko; Takahashi, Mamiko; Maruhashi, Tomoko; Udaka, Kengo; Iwasa, Masami; Fujii, Shiro; Nakamura, Shingen; Abe, Masahiro
Abstract: Disseminated Cryptosporidium infection results in manifestations similar to those of graft‐versus‐host disease (GVHD), which hampers the detection of Cryptosporidium infection after allogeneic hematopoietic stem cell transplantation. Surveillance of oocysts on the surface of intestinal epithelial cells is needed for early and appropriate detection of Cryptosporidium infection in transplant recipients on immunosuppressants with severe intractable diarrhea. We present the first case of Cryptosporidium meleagridis infection in Japan after allogeneic cord blood transplantation.